2021
DOI: 10.3390/molecules26195790
|View full text |Cite
|
Sign up to set email alerts
|

Role of 5-HT1A Receptor in Vilazodone-Mediated Suppression of L-DOPA-Induced Dyskinesia and Increased Responsiveness to Cortical Input in Striatal Medium Spiny Neurons in an Animal Model of Parkinson’s Disease

Abstract: L-DOPA therapy in Parkinson’s disease (PD) is limited due to emerging L-DOPA-induced dyskinesia. Research has identified abnormal dopamine release from serotonergic (5-HT) terminals contributing to this dyskinesia. Selective serotonin reuptake inhibitors (SSRIs) or 5-HT receptor (5-HTr) agonists can regulate 5-HT activity and attenuate dyskinesia, but they often also produce a loss of the antiparkinsonian efficacy of L-DOPA. We investigated vilazodone, a novel multimodal 5-HT agent with SSRI and 5-HTr1A partia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 82 publications
2
1
0
Order By: Relevance
“…Consistent with previous research (Altwal et al, 2021; Guimarães et al, 2022), our data revealed that MSNs in dyskinetic animals exhibited reduced spike onset latency following cortical stimulation compared with sham‐operated animals, suggesting increased MSN excitability. The onset latency, which reflects the time required to respond to stimulus onset, is a functional property of MSNs.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with previous research (Altwal et al, 2021; Guimarães et al, 2022), our data revealed that MSNs in dyskinetic animals exhibited reduced spike onset latency following cortical stimulation compared with sham‐operated animals, suggesting increased MSN excitability. The onset latency, which reflects the time required to respond to stimulus onset, is a functional property of MSNs.…”
Section: Discussionsupporting
confidence: 92%
“…Specifically, L-DOPA-induced dyskinesias were assessed (see [ 14 ] for detailed descriptions of these behaviors and their quantification). All rats with such dopamine lesions developed mid- to high levels of L-DOPA-induced dyskinesias during the repeated L-DOPA treatment (see [ 14 ]), similar to our previously reported findings after such treatments [ 16 ]. In animals co-treated with TP-10 (6/LD + TP), dyskinesias were partly inhibited (in preparation).…”
Section: Methodssupporting
confidence: 90%
“…Sleep Disorders: Including Sleep paralysis, Hypnagogic hallucination, Rapid eye movements sleep abnormal, Sleep terror, Terminal insomnia, Tachyphrenia, these could stem from Vilazodone's modulation of neurotransmitters and the sleep cycle. As a selective serotonin reuptake inhibitor and 5-HT1A receptor agonist, Vilazodone impacts the levels of serotonin and other neurotransmitters like dopamine and norepinephrine [18,19]. This influence might lead to sleep paralysis (due to an imbalance in REM sleep regulation), Hypnagogic hallucination, and Tachyphrenia (due to alterations in cognitive processes and perception).…”
Section: Discussionmentioning
confidence: 99%